New species of Callichromatini Swainson, 1840. (Coleoptera, Cerambycidae). New Cerambycidae from Vietnam. Part 6 - Vives, Eduard; Pham, Hong Thai (Zootaxa, 2017)
Three new species of Cerambycidae, Callichromatini from Vietnam are described: Aphrodisium lingafelteri sp. nov., Mimochelidonium vietnamicum sp. nov., and Polyzonus (Striatopolyzonus) tonkinensis sp. nov. The genus Mimochelidonium Bentanachs & Drouin is recorded as new for the fauna of Vietnam.